Analisis Aksi Demonstrasi Mahasiswa Menolak RUU KUHP dan RUU KPK: Antara Sikap Kritis dan Narsis - Jiwandono, Ilham Syahrul; Oktaviyanti, Itsna (Prodi Sosiologi Agama, 2020)
Various policies issued by the legislative and executive bodies provoke various demonstrations carried out by students in various regions in Indonesia. This demonstration is a form of student attention to the sustainability of the Indonesian state. There are differences in the nuances of the demonstration that were conducted by students a few decades ago and now. The demonstration is now more of a place for student narcissism. This study analyzes the students' critical and narcissistic attitudes in demonstrations. The research approach uses descriptive qualitative. Retrieval of data through interviews, observation, and documentation. The research phase includes prefield, field, and data analysis. The location of the study was at the University of Mataram, Elementary School Teacher Education Study Program. The data sources are students in the 3rd and 5th semesters and lecturers at the University of Mataram, Elementary School Teacher Education Program. The results showed: (1) The demonstration was triggered by students' objections to the RUU KPK and the RUU KUHP. (2) Demonstrations bring positive and negative impacts for students. (3) There was a change in the nuances of the demonstration conducted by students. If all this time the demonstration was identical to the criticism of students, it has now developed into a narcissistic arena. (4). Student narcissism in demonstrations is based on their obsession to get recognition and appreciation from the community.